The Effect of Cu Ohmic Contact on Photoelectrochemical Property of S-CuO Thin Film Photocathodes - Aziz Amrullah; Gunawan Gunawan; Nor Basid Adiwibawa Prasetya (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2019)
The development of semiconductor materials as photocathodes that have excellent performance is significant for the photoelectrochemical reaction of hydrogen evolution. The thin film of sulfur-doped Copper (II) oxide (S-CuO) was successfully synthesized using the cyclic voltammetry method. Investigation of photoelectrochemical properties of S-CuO photocathodes, including current density, onset potential, applied photon to current efficiency (ABPE), and bandgap had been carried out. It was reported that the Cu ohmic contact affected the photoelectrochemical properties and the stability of the thin film. The presence of Cu ohmic contact can improve the performance of S-CuO thin film photocathodes. The S-CuO TU 20 mM thin film has the best response with a current density of -0.923 mA/cm2, an onset potential of 0.59 V, and ABPE of 0.21%. Stability occurred at pH 7 in 0.2M NaH2PO4. The optical analysis showed S-CuO TU 20 mM bandgap of 1.7 eV.